Coupling of Redox and Structural States in Cytochrome P450 Reductase Studied by Molecular Dynamics Simulation - Mikuru Iijima (Nature Portfolio, 2019)
Abstract Cytochrome P450 reductase (CPR) is the key protein that regulates the electron transfer from NADPH to various heme-containing monooxygenases. CPR has two flavin-containing domains: one with flavin adenine dinucleotide (FAD), called FAD domain, and the other with flavin mononucleotide (FMN), called FMN domain. It is considered that the electron transfer occurs via FAD and FMN (NADPH → FAD → FMN → monooxygenase) and is regulated by an interdomain open-close motion. It is generally thought that the structural state is coupled with the redox state, which, however, has not yet been firmly established. In this report, we studied the coupling of the redox and the structural states by full-scale molecular dynamics (MD) simulation of CPR (total 86.4 μs). Our MD result showed that while CPR predominantly adopts the closed state both in the oxidized and reduced states, it exhibits a tendency to open in the reduced state. We also found a correlation between the FAD-FMN distance and the predicted FMN-monooxygenase distance, which is embedded in the equilibrium thermal fluctuation of CPR. Based on these results, a physical mechanism for the electron transfer by CPR is discussed.